From Likes to Enrolment: How Social Media Shapes Decision-Making Among Prospective Students - Saksono, Lalang; Sugiono, Edi; Lestari, Rahayu; Hasanudin; Nurwulandari, Andini (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates how social media-driven digital engagement shapes enrolment decisions among prospective students at Universitas Djuanda Bogor, focusing on the interplay between online interactions and institutional choice in Indonesia’s higher education landscape. A mixed-methods approach was employed, combining quantitative surveys (n = 320) to measure the frequency and type of social media interactions, qualitative interviews (n = 25) to explore subjective experiences, and analytics data from the university’s official platforms. Data triangulation was performed to identify patterns in digital engagement and its linkage to enrolment intent. A strong positive correlation was found between active digital engagement (e.g., content sharing, peer discussions, and virtual campus tours) and enrolment likelihood (r = 0.72, p < 0.01). Prospective students who engaged with user-generated content (UGC) were 1.8 times more likely to apply than those who only consumed official posts. This outcome arises because peer narratives and authentic student experiences shared on social media reduced perceived uncertainty about academic quality and campus life, while algorithmic personalization amplified institutional visibility among target demographics. The findings underscore the need for universities to strategically integrate UGC and peer-driven storytelling into their recruitment strategies. Additionally, this study advances the discourse on digital inequality by highlighting how socio-economic disparities in internet access may skew enrolment advantages toward tech-savvy, urbanized applicants. This research introduces a contextualized framework linking algorithmic affordances of social media to enrolment behaviour in a developing economy, contrasting prior studies focused on Western institutions.